A pilot study investigating the effect of pedalling exercise during dialysis on 6-min walking test and hand grip and pinch strength. Issue 4 (April 2019) - Desai, Manasi; Mohamed, Ahmed; Davenport, Andrew
Introduction: Haemodialysis patients are at an increased risk of sarcopenia. Physical inactivity is now recognised as a major cause of muscle wasting in haemodialysis patients. It is unclear as to what and how much exercise is required to show benefit. We therefore performed a pilot study of cycling during haemodialysis. Methods: Patients underwent a progressive submaximal individualised cycling exercise, 3× a week during haemodialysis for 4 months using bed-cycle ergometers. Body composition was measured by multifrequency segmental bioimpedance and muscle function by 6-min walking test, and hand grip strength and pinch strength. Results: In total, 56% of patients in a dialysis centre fulfilled exercise study inclusion criteria and 13 (72.2%) of 18 patients completed the exercise programme, with the mean age of 64.0 ± 16.6 years and 76.9% being male. The 6-min walking test increased following exercise from 349 ± 105 to 398 ± 94.2 m, p < 0.05, as did both hand grip strength and pinch strength, with 20.4 ± 9.1 versus 23.4 ± 9.9 kg, p < 0.01, and 4.3 ± 1.8 versus 5.9 ± 2.4 kg, p < 0.05, respectively. There were no changes in appendicular muscle mass or other body composition detected with bioimpedance in either the exercise group, or 21 control patients, propensity matched for body composition, comorbidity and frailty. Muscle strength did not change in the control group. Haemodialysis sessional Kt/Vurea was greater at the end of the exercise programme compared to controls (1.63 ± 0.63 vs 1.21 ± 0.12, p < 0.01). Conclusion: The majority of dialysis centre patients met our exercise study entry criteria and could potentially benefit from cycling during haemodialysis. We found that muscle function and strength improved after a 4-month, thrice weekly cycling exercise programme.